PENGEMBANGAN MEDIA DAN SUMBER BELAJAR CETAK UNTUK JENJANG MI/SD - Nabila, Putri; Nasution, Nurul Ilmi; Muhammad Fahri (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Printed media and learning resources still play a crucial role in supporting the learning process at the elementary (MI/SD) level. This study aims to develop printed learning media that align with the characteristics of students and the demands of the curriculum. This research employs a library research method by reviewing various relevant literatures on media development, the characteristics of elementary school students, and instructional design principles. The findings indicate that printed media designed with attention to visual aspects, communicative language, and content relevance can enhance the effectiveness of learning. Therefore, the development of high-quality printed media is considered a key strategy in supporting the success of the teaching and learning process at the MI/SD level.